Self-management: A comprehensive approach to improve quality of life among people living with HIV in Indonesia - Fauzi, Achmad; Anggraini, Nofa; Fatkhurohman, Novy (Belitung Raya Foundation, Indonesia, 2021)
Background: People living with HIV (PLWH) today have to deal with a chronic condition that requires efficient self-management due to increased longevity. Self-management interventions have been shown to improve physical and psychological symptoms as well as clinical results in chronic diseases. However, few studies have investigated the effect of self-management on quality of life (QOL) among PLWH in Indonesia. Objective: To examine the effect of a self-management program on QOL among PLWH in Indonesia. Methods: This was a quasi-experimental study with a comparison group in a general hospital in Jakarta, Indonesia. Of the 114 recruited PLWH, 57 were assigned to the intervention group and 57 to the comparison group. The self-management group attended a four-week program workshop. The intervention consisted of five sessions: need assessment and goal setting, maintaining a healthy lifestyle, educational participation to increase communication and self-esteem, and evaluation. The comparison group received standard educational material throughout the leaflet regarding HIV prevention. The post-test assessment was conducted immediately after intervention (T1) and two months (T2) after the intervention in both groups. QOL was measured using the World Health Organization Quality of Life (WHOQOL)-HIV brief Bahasa version. The estimations were obtained using fixed-effect regressions. The differences between T0, T1, and T2 for the intervention and comparison groups were evaluated and compared using the DI Differences method (DID). Results: The self-management program improved outcomes relative to the comparison group at T1: 1) overall QOL score increased 8.7% (95% CI 0.021–0.149), 2) physical domain saw a modest increased 8.8% (95% CI 0.017–0.125), 3) psychological domain increased 23.5 % (95% CI 0.085–0.689), and 4) environmental domain showed a modest increase of 18.7% (95% CI 0.053–0.371). At T2, the total QOL score and the physical, psychological, and environmental dimensions were significantly improved compared to the comparison group. Conclusion: The self-management program appears to improve the QOL of the life of PLWH. Nurses are advised to provide PLWH with self-management training. Future research on self-management intervention would need to be refined further to ensure that each community achieves consistent intervention outcomes.